Model game edukasi pembelajaran bahasa arab berbasis android untuk anak-anak - Sandy Ilham Hakim Syasri; Nazruddin Safaat H; Muhammad Irsyad; Febi Yanto (Universitas Muhammadiyah Riau, 2023)
In the era of globalization, understanding Arabic is becoming increasingly important, and starting language learning early provides an invaluable competitive advantage. Games as learning media can increase students' motivation and interest in learning. This educational game is designed in an interesting way, such as quiz and puzzle and this game is built based on android with high flexibility allowing children to learn anytime and anywhere, using devices such as smartphones and tablets. With the approach of playing while learning, children are believed to be able to understand Arabic without feeling burdened. The development of this game uses the MDLC (Multimedia Development Life Cycle) method with 6 stages including concept, design, material collecting, assembly, testing, distribution, and testing the effectiveness of the game by running tests using black box and User Acceptance Test (UAT) and using Unity software in building games that can be run on android smartphones. The results of Black box Testing obtained test results from the learning mode function, play mode, settings and all buttons in the game run well without any errors. From the results of UAT testing by giving the game to 13 respondents and getting a score of 90% with a very good category which means that the Android-based Arabic Language Introduction Game is feasible as a new learning media innovation and can increase children's interest.